SPIRITUALITAS KAUM FUNDAMENTALIS - Musyafiq, Ahmad (IAIN Walisongo Semarang, 2012)
Abstract One of the most important phenomenon that characterized the begining of XXI century is the blossom of spiritual activities. Broadly speaking, there are two model of spiritualities: institutional spirituality like tarekat and non-institutional spirituality. This article focus on how religious study that so far executed by Hizbut Tahrir Indonesia Central Java, which much pertained to the main themes of tasawuf study, like purification of heart, tawakkal, ikhlas, sabar, etc. But because they rejected tasawwuf, so they applied the term of spirituality. *** Salah satu fenomena terpenting yang yang mencirikan awal abad ke XXI adalah berkembangnya aktifitas spiritual. Secara luas, ada dua model spiritualitas: spiritualitas institusional seperti tarikat dan spiritualitas non-institusional. Artikel ini memfokuskan pada bagaimana kajian agama yang selama ini dilakukan oleh Hizbut Tahrir Indonesia in central Java yang terkait erat dengan tema-tema utama dalam kajian tasawuf seperti pemurnian hati, tawakkal, ikhlas, sabar, dan lain-lain. Namun karena mereka menolak tasawuf maka mereka mereka menggunakan spiritualitas. Keywords: spiritualitas, fundamentalisme, HTI